THE ACCOUNTING EXCHANGE. - Littleton, A. C. (The Accounting Review, 1943)
The fact that the complicated business of making war can be epitomized for certain purposes into a few guiding principles suggests that accounting also may rest upon certain leading ideas which we may call principles. The military strategist would not thumb through a pocket list to choose the principle to be applied next to his situation. Neither would an accountant. Principles probably serve their purpose best after their essence and their interrelations have been made so thoroughly a part of a man's thinking processes as to have been forgotten as verbal propositions. In times like these, generalizations about the science of making war are interesting for their own sake to laymen. But they can be of more than passing interest to accountants because they illustrate so well the useful art of generalization. About a year ago a compact summary of the principles of war was published, as of October 1943. The nine principles stated in the summary are briefly summarized in this article to give further emphasis on the factor of interdependence.